Identification of Sources of Resistance in Sesame Against Leaf Webber and Capsule Borer (Antigastra Catalaunalis Dup.) (Bangladesh Journal of Botany, 2021)
The 197 entries including two checks (SI-250 Resistance check and TC-25 Susceptible check) of sesame (Sesamum indicum L.) representing varied geographic and genetic diversity were tested at three diverse climatic locations of India viz., Jabalpur, Mandor and Vriddhachalam, against leaf webber and capsule. None of the screened entry was found to be free from infestation by leaf webber and capsule borer. The average plant, flower and capsule damage over the locations varied from 6.58 to 27.17, 7.80 to 23.71 and 3.33 to 15.43%, respectively. At vegetative stage, the entries SI-0018-B (6.33%) and IS-353-A (6.58%) at flowering, the entry KMR-7 (7.80%) and at capsule stage, the entries SI-0018-B (3.33%), MT-67-25 (3.65%) and RJS- 56-A (3.80%) were recorded the lowest damage. Further, the response of promising entries under artificial pest load conditions over the locations showed that the entry SI-271-B was superior to others with respect to lowest plant and flower damage while at capsule stage, the entry NIC-8510-B was superior. Under artificial pest load condition, the entries SI-271-B, NIC-9839 and MT-67-25 showed the lowest damage whereas under natural condition, the entries IS-178-C and SP-3267 were superior to others with respect to lowest damage. The feeding preference studies showed that the entries SI-271-B, IS-178-C, MT-67-25 and S-OO-17-B were least preferred by the leaf webber and capsule borer and recorded the lowest leaf area damage.Bangladesh J. Bot. 50(3): 565-575, 2021 (September)